Evaluation of metatranscriptomic protocols and application to the study of freshwater microbial communities. Issue 6 (17th June 2014) - Tsementzi, Despina; Poretsky, Rachel; Rodriguez‐R, Luis M.; Luo, Chengwei; Konstantinidis, Konstantinos T.
Summary Metatranscriptomics of environmental samples enables the identification of community activities without a priori knowledge of taxonomic or functional composition. However, several technical challenges associated with the RNA preparation protocols can affect the relative representation of transcripts and data interpretation. Here, seven replicate metatranscriptomes from planktonic freshwater samples (Lake Lanier, USA) were sequenced to evaluate technical and biological reproducibility of different RNA extraction protocols. Organic versus bead‐beating extraction showed significant enrichment for low versus high G + C% mRNA populations respectively. The sequencing data were best modelled by a negative binomial distribution to account for the large technical and biological variation observed. Despite the variation, the transcriptional activities of populations that persisted in year‐round metagenomes from the same site consistently showed distinct expression patterns, reflecting different ecologic strategies and allowing us to test prevailing models on the contribution of both rare biosphere and abundant members to community activity. For instance, abundant members of the Verrucomicrobia phylum systematically showed low transcriptional activity compared with other abundant taxa. Our results provide a practical guide to the analysis of metatranscriptomes and advance understanding of the activity and ecology of abundant and rare members of temperate freshwater microbial communities.